ADMINISTRATION APPLYING GOOD GOVERNANCE AND PARTICIPATIVE MANAGEMENT AFFECTINGTHE PERFORMANCE EFFECTIVENESS OF MUNICIPALITY ORGANIZATION IN TAK PROVINCE - kongyamast, prakob (Life Sciences and Environment Journal, 2017)
This research aimed at: (1) studying the administration applying good governance, participative management, and the performance effectiveness of Municipality in Tak Province; (2) investigating the relationship between good governance administration and participative management that affect the performance effectiveness of Tak Municipality; and (3) proposing guidelines to develop the performance effectiveness of the organization. The study is a mixed method research. The sample populations were 255 including administrators, civil servants, employees, and members of Tak Municipality. The populations were selected using stratified random sampling and simple random techniques. Survey questionnaire was utilized to collect the information. In addition, an in-depth interview was administrated to 18 mayors of Tak Municipality. The research findings revealed that the relationship between good governance administration, participative management, and the performance effectiveness were correlated in the same direction (r=0.790-0.0841 at 0.01 level of significance. Factors influencing good governance administration consisted of accountability, responsiveness, transparency, equity and inclusiveness, participation on evaluation, rule of law, morality and consensus orientation, participations in the implementation, benefits, and decision-making process.